Protection of Indonesian Migrant Workers (Pekerja Migran Indonesia, PMI) in Problems Abroad - Saraswati, Pipit; Susanti, Rahtami; Setiawan, Bayu (UMPurwokerto Law Review, 2021)
The lack of job opportunities in the country has pushed thousands of Indonesian citizens to seek work abroad. The Indonesian Migrant Workers Protection Agency (Badan Pelindungan Pekerja Migran Indonesia, BP2MI) released the placement of Indonesian Migrant Workers (Pekerja Migran Indonesia, PMI) in 2018 (April) period as many as 23,431 people and 2019 as many as 25,489 people. Meanwhile, the Central Statistics Agency (Badan Pusat Statistik, BPS) stated that 520 Indonesian Migrant Workers had problems in 2018 (April) period and 846 people in 2019. This study aims to determine the protection of Indonesian Migrant Workers who have problems abroad and the government's obstacles in protecting Indonesian Migrant Workers who have problems abroad. This study uses a normative juridical approach. That is the approach taken to legal materials, both primary, secondary, and tertiary legal materials by examining theories, concepts, legal principles, and laws and regulations related to this research. The results of this study are first, protection for Indonesian Migrant Workers who have problems abroad, namely technical protection in the form of providing shelter, juridical protection in the form of legal assistance to PMI who are in a legal process, and political protection in the form of bilateral agreements. between Indonesia and recipient countries regarding the placement and protection of PMIs. Second, the obstacles faced by the government in protecting PMIs are the lack of legal awareness of PMI candidates, the weakness of the supervisory system, the difficulty of registering PMIs in the destination country, and the difficulty of providing lawyers to assist PMIs who conflict with the law. To reduce problematic PMI cases abroad, local governments must realize the existence of a Migrant Workers Care Village (Desa Peduli Migrant Workers, DESBUMI) in every village. Keywords: Protection, Migrant Workers, Problems